Preparation process of waterproof paint for roads and bridges
By polymerizing and chain extension reaction with isocyanate monomers and other materials, and ionically crosslinking with nanocellulose and copper salts, the problem of poor waterproof and corrosion resistance and mechanical properties of polyurethane coatings is solved, and higher waterproof and corrosion resistance and mechanical properties are achieved, and it is suitable for roads and bridges and other fields.
Patent Information
- Application Number
- CN202510174914.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-18
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2045-02-18
AI Technical Summary
Polyurethane coatings have poor waterproof and corrosion resistance and mechanical properties in roads and bridges.
A preparation process is adopted to polymerize and chain extension reactions of polyester polyols with isocyanate monomers, 4-N,N-bis(2-hydroxyethyl)aminepyridine-2-carboxylic acid and other materials to form aqueous polyurethanes and ionic crosslinks with additives such as nanocellulose and copper salts to improve the interface bonding performance and waterproof and corrosion resistance of the coating.
It significantly improves the waterproof and corrosion resistance and mechanical properties of polyurethane coatings, forming higher pencil hardness, impact resistance and water resistance, and is suitable for practical applications in roads and bridges and other fields.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a preparation process of a waterproof coating for roads and bridges. Background Art
[0002] Paints are widely used in roads, bridges, cars, ships, machinery and equipment, etc., playing the role of waterproofing, anti-corrosion, and beautiful decoration. Waterborne polyurethane uses water as a solvent, does not contain toxic volatile solvents, is green and environmentally friendly, and is widely used. Traditional polyester-based waterborne polyurethane has poor water resistance and is easily hydrolyzed when it absorbs water, resulting in poor mechanical properties and anti-corrosion properties of the paint film. At present, the modification methods of polyurethane coatings include cross-linking modification, filling modification, etc.
[0003] Nanocrystalline cellulose is cheap and easy to obtain, has high mechanical strength, is green and environmentally friendly, and is widely used in materials such as coatings, inks, and plastics. The Chinese patent with announcement number CN108610721B discloses a flame retardant modified polyurethane curing agent and a preparation method and a two-component polyurethane coating. The microcrystalline cellulose solution is mixed with nano magnesium hydroxide to obtain composite microspheres, which are then mixed and modified with 4,4-diphenylmethane diisocyanate to improve the hardness and flame retardancy of the curing agent on the polyurethane coating film. However, the patent does not improve the waterproof and anti-corrosion properties of the polyurethane coating, which is not conducive to the practical application of polyurethane coatings in roads and bridges. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a preparation process for a waterproof coating for roads and bridges, which solves the problems of poor waterproof and anti-corrosion performance and poor mechanical properties of polyurethane coatings.
[0005] A preparation process of a waterproof coating for roads and bridges comprises the following steps: adding polyester polyol into a reaction container, adding isocyanate monomer and dibutyltin dilaurate after drying and dehydration, introducing nitrogen, heating to 70-80°C, reacting for 2-2.5 hours, lowering the temperature to 40-45°C, adding acetone and 4-N,N-di(2-hydroxyethyl)aminopyridine-2-carboxylic acid, reacting for 40-60 minutes, adding water, nanocellulose and copper salt, stirring for 6-10 hours, and finally adding a neutralizing agent triethylamine, a pigment, a dispersant and a defoaming agent, and shearing and dispersing to obtain a waterproof coating for roads and bridges.
[0006] Preferably, the molar ratio of polyester polyol to isocyanate monomer n(-OH):n(-NCO) is 1:(2.6-2.8).
[0007] Preferably, the molar ratio of the isocyanate monomer to 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid is 1:(1-1.1).
[0008] Preferably, the isocyanate monomer is any one of toluene-2,4-diisocyanate, isophorone diisocyanate, and 4,4'-diphenylmethane diisocyanate.
[0009] Preferably, the mass of the nanocellulose is 10-25% of the total mass of the polyester polyol, the isocyanate monomer and the 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid.
[0010] Preferably, the mass of the copper salt is 0.5-1.4% of the total mass of the polyester polyol, the isocyanate monomer and the 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid.
[0011] Preferably, the copper salt is cuprous chloride or cupric nitrate.
[0012] Preferably, the preparation process of 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid is: (1) Add water, propionic acid and methyl 4-aminopyridine-2-carboxylate to a reaction vessel, add a tetrahydrofuran solution of ethylene oxide at 0-5°C, control the molar ratio of methyl 4-aminopyridine-2-carboxylate to ethylene oxide to be 1:(2.4-3), then react at 10-15°C for 18-30h, remove tetrahydrofuran and low-boiling substances by vacuum distillation, extract the aqueous phase with ethyl acetate, vacuum distill the ethyl acetate phase, and dry to obtain methyl 4-N,N-di(2-hydroxyethyl)aminopyridine-2-carboxylate.
[0013] (2) Add 4-N,N-di(2-hydroxyethyl)aminopyridine-2-carboxylic acid methyl ester and a sodium hydroxide aqueous solution with a concentration of 2.8-4 mol / L to methanol, heat to 85-90°C, condense and reflux for 5-8 hours, remove methanol by vacuum distillation, add hydrochloric acid dropwise to the aqueous phase to precipitate a large amount of precipitate, filter, and dry to obtain 4-N,N-di(2-hydroxyethyl)aminopyridine-2-carboxylic acid. The reaction formula is: .
[0014] Compared with the prior art, the present invention has the following beneficial effects: The invention conducts a ring-opening addition reaction between 4-aminopyridine-2-carboxylic acid methyl ester and ethylene oxide, then hydrolyzes the ester group to obtain 4-N,N-di(2-hydroxyethyl)aminopyridine-2-carboxylic acid, which is used as a water-based carboxylic acid chain extender for polyurethane, and is subjected to a polymerization chain extension reaction with polyester polyol and isocyanate monomer to obtain water-based polyurethane, which is then compounded with nano-cellulose, copper salt, pigment and the like to obtain a waterproof coating for roads and bridges.
[0015] The waterborne polyurethane coating emulsion of the invention does not delaminate and has excellent storage stability. The added copper ions form coordination effects with the pyridine-2-carboxylic acid of the polyurethane and the hydroxyl group of the nanocellulose respectively, so that the copper ions play the role of a crosslinking agent, and the polyurethane and the nanocellulose are ionically crosslinked, thereby improving the interface bonding performance of the polyurethane and the nanocellulose, making the nanocellulose play a better reinforcing role, and the coating film has higher pencil hardness, impact resistance and mechanical properties.
[0016] The polyurethane and nanocellulose of the present invention are cross-linked by ions to form a tight molecular chain cross-linking network, which can inhibit water molecules and corrosive media such as acids, alkalis and salts from entering the interior of the polyurethane paint film, so that the paint film exhibits higher water resistance and salt spray resistance, and has better waterproof and anti-corrosion performance. It has good practical applications in the fields of roads and bridges. DETAILED DESCRIPTION
[0017] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] Nanocellulose, content 99.9%, was purchased from Hubei Watson Chemical Technology Co., Ltd. Polyester polyol, model Evonik Dynacoll 7130, was purchased from Wuhan Jinqu New Materials Co., Ltd.
[0019] Embodiment 1: (1) 30 mL of water, 2.3 mL of propionic acid, and 50 mmol of 4-aminopyridine-2-carboxylic acid methyl ester were added to a reaction vessel, and 75 mL of a tetrahydrofuran solution containing 120 mmol of ethylene oxide was added at 5°C, followed by reaction at 10°C for 30 h. The tetrahydrofuran and low-boiling substances were removed by vacuum distillation, the aqueous phase was extracted with ethyl acetate, the ethyl acetate phase was vacuum distilled, and dried to obtain 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid methyl ester.
[0020] (2) Add 8 g of 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid methyl ester and 75 mL of 3.5 mol / L sodium hydroxide aqueous solution to 100 mL of methanol, heat to 85°C, condense and reflux for 7 h, remove methanol by distillation under reduced pressure, add concentrated hydrochloric acid dropwise to the aqueous phase, precipitate a large amount of precipitate, filter and dry to obtain 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid.
[0021] (3) Add polyester polyol (molecular weight 2000, total hydroxyl -OH content 0.1 mol) to the reaction vessel, dry and dehydrate, add 0.28 mol toluene-2,4-diisocyanate, 0.3 g dibutyltin dilaurate, introduce nitrogen, heat to 75 ° C, react for 2.5 h, reduce the temperature to 45 ° C, add 30 mL acetone, 0.308 mol 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid, react for 60 min, add 400 mL water, nanocellulose, and cuprous chloride, and control the mass of nanocellulose to be 10% of the total mass of polyester polyol, toluene-2,4-diisocyanate and 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid. The mass of cuprous chloride is 0.5% of the total mass of polyester polyol, toluene-2,4-diisocyanate and 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid. The mixture was stirred for 6 h, and finally 42 mL of neutralizing agent triethylamine, 46 g of pigment titanium dioxide, 2.7 g of dispersant, and 1.3 g of defoaming agent were added, and the mixture was sheared and dispersed to obtain a waterproof coating for roads and bridges.
[0022] Embodiment 2: (1) Add 40 mL of water, 2.2 mL of propionic acid, and 50 mmol of 4-aminopyridine-2-carboxylic acid methyl ester to a reaction vessel, add 75 mL of a tetrahydrofuran solution containing 130 mmol of ethylene oxide at 5°C, and then react at 15°C for 24 hours. Distill under reduced pressure to remove tetrahydrofuran and low-boiling substances, extract the aqueous phase with ethyl acetate, distill the ethyl acetate phase under reduced pressure, and dry to obtain 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid methyl ester.
[0023] (2) Add 8 g of 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid methyl ester and 65 mL of 4 mol / L sodium hydroxide aqueous solution to 100 mL of methanol, heat to 85°C, condense and reflux for 8 h, remove methanol by distillation under reduced pressure, add concentrated hydrochloric acid dropwise to the aqueous phase, precipitate a large amount of precipitate, filter and dry to obtain 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid.
[0024] (3) Add polyester polyol (molecular weight 2000, total hydroxyl -OH content 0.1 mol) into the reaction vessel, add 0.26 mol 4,4'-diphenylmethane diisocyanate and 0.32 g dibutyltin dilaurate after drying and dehydration, introduce nitrogen, heat to 70 °C, react for 2.5 h, reduce the temperature to 40 °C, add 40 mL acetone and 0.26 mol 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid, react for 40 min, add 400 mL water, nanocellulose, and copper nitrate, and control the mass of nanocellulose to be 15% of the total mass of polyester polyol, 4,4'-diphenylmethane diisocyanate and 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid. The mass of copper nitrate is 0.8% of the total mass of polyester polyol, 4,4'-diphenylmethane diisocyanate and 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid. Stir for 10 hours, and finally add 36mL of neutralizer triethylamine, 56g of pigment titanium dioxide, 3.4g of dispersant, and 1.3g of defoamer, and shear and disperse to obtain a waterproof coating for roads and bridges.
[0025] Embodiment 3: (1) Add 40 mL of water, 2.5 mL of propionic acid, and 50 mmol of 4-aminopyridine-2-carboxylic acid methyl ester to a reaction vessel, add 60 mL of a tetrahydrofuran solution containing 150 mmol of ethylene oxide at 0°C, and then react at 15°C for 18 hours. Distill under reduced pressure to remove tetrahydrofuran and low-boiling substances, extract the aqueous phase with ethyl acetate, distill the ethyl acetate phase under reduced pressure, and dry to obtain 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid methyl ester.
[0026] (2) Add 8 g of 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid methyl ester and 90 mL of 2.8 mol / L sodium hydroxide aqueous solution to 80 mL of methanol, heat to 90°C, condense and reflux for 5 h, remove methanol by distillation under reduced pressure, add concentrated hydrochloric acid dropwise to the aqueous phase, precipitate a large amount of precipitate, filter and dry to obtain 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid.
[0027] (3) Add polyester polyol (molecular weight 2000, total hydroxyl-OH content 0.1 mol) to the reaction vessel, add 0.274 mol isophorone diisocyanate and 0.3 g dibutyltin dilaurate after drying and dehydration, introduce nitrogen, heat to 80 °C, react for 2 h, reduce the temperature to 45 °C, add 40 mL acetone and 0.28 mol 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid, react for 60 min, add 500 mL water, nanocellulose, and cuprous chloride, and control the mass of nanocellulose to be 20% of the total mass of polyester polyol, isophorone diisocyanate and 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid. The mass of cuprous chloride is 1.1% of the total mass of polyester polyol, isophorone diisocyanate and 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid. The mixture was stirred for 10 hours, and finally 40 mL of a neutralizing agent, triethylamine, 40-56 g of a pigment, titanium dioxide, 2.2-3.4 g of a dispersant, and 1.3-1.6 g of a defoaming agent were added, and the mixture was sheared and dispersed to obtain a waterproof coating for roads and bridges.
[0028] Embodiment 4: (1) Add polyester polyol (molecular weight 2000, total hydroxyl-OH content 0.1 mol) into a reaction vessel, add 0.27 mol isophorone diisocyanate and 0.3 g dibutyltin dilaurate after drying and dehydration, introduce nitrogen, heat to 80°C, react for 2 h, reduce the temperature to 45°C, add 40 mL acetone and 0.278 mol 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid (prepared in Example 1), react for 60 min, add 450 mL water, nanocellulose, and cuprous chloride, and control the mass of nanocellulose to be 25% of the total mass of polyester polyol, isophorone diisocyanate and 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid. The mass of cuprous chloride is 1.4% of the total mass of polyester polyol, isophorone diisocyanate and 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid. The mixture was stirred for 10 h, and finally 40 mL of neutralizing agent triethylamine, 44 g of pigment titanium dioxide, 2.6 g of dispersant, and 1.6 g of defoaming agent were added, and the mixture was sheared and dispersed to obtain a waterproof coating for roads and bridges.
[0029] Comparative Example 1: (1) Add polyester polyol (molecular weight 2000, total hydroxyl-OH content 0.1 mol) to a reaction container, add 0.28 mol toluene-2,4-diisocyanate and 0.3 g dibutyltin dilaurate after drying and dehydration, introduce nitrogen, heat to 75°C, react for 2.5 h, reduce the temperature to 45°C, add 30 mL acetone, 0.308 mol 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid (prepared in Example 1), react for 60 min, add 400 mL water and nanocellulose, and control the mass of nanocellulose to be 10% of the total mass of polyester polyol, toluene-2,4-diisocyanate and 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid. Stir for 6 h, finally add 42 mL neutralizer triethylamine, 46 g pigment titanium dioxide, 2.7 g dispersant and 1.3 g defoamer, and shear and disperse to obtain a waterproof coating for roads and bridges.
[0030] Comparative Example 2: (1) Add polyester polyol (molecular weight 2000, total hydroxyl-OH content 0.1 mol) to a reaction container, add 0.28 mol toluene-2,4-diisocyanate and 0.3 g dibutyltin dilaurate after drying and dehydration, introduce nitrogen, heat to 75°C, react for 2.5 h, reduce the temperature to 45°C, add 30 mL acetone, 0.308 mol 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid methyl ester (prepared in Example 1), react for 60 min, add 400 mL water and nanocellulose, and control the mass of nanocellulose to be 10% of the total mass of polyester polyol, toluene-2,4-diisocyanate and 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid. Stir for 6 h, finally add 46 g pigment titanium dioxide, 2.7 g dispersant and 1.3 g defoamer, and shear and disperse to obtain a waterproof coating for roads and bridges.
[0031] Comparative Example 3: (1) Add polyester polyol (molecular weight 2000, total hydroxyl -OH content 0.1 mol) into the reaction vessel, dry and dehydrate, add 0.28 mol toluene-2,4-diisocyanate, 0.3 g dibutyltin dilaurate, introduce nitrogen, heat to 75 ° C, react for 2.5 h, reduce the temperature to 45 ° C, add 30 mL acetone, 0.308 mol 2,2-dihydroxymethylpropionic acid, react for 60 min, add 400 mL water, nanocellulose, cuprous chloride, and control the mass of nanocellulose to be 10% of the total mass of polyester polyol, toluene-2,4-diisocyanate and 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid. The mass of cuprous chloride is 0.5% of the total mass of polyester polyol, toluene-2,4-diisocyanate and 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid. The mixture was stirred for 6 h, and finally 42 mL of neutralizing agent triethylamine, 46 g of pigment titanium dioxide, 2.7 g of dispersant, and 1.3 g of defoaming agent were added, and the mixture was sheared and dispersed to obtain a waterproof coating for roads and bridges.
[0032] The storage stability of the coating is tested according to GB / T 6753.3-1986 standard, and the storage time is 6 months. The pencil hardness of the paint film is tested according to GB / T 6739-2022 standard, and the curing condition is baking at 80℃ for 5h. The impact resistance is tested according to GB / T 1732-2020 standard. The water resistance is tested according to GB / T 1733-1993 standard. The salt spray resistance is tested according to GB / T 1771-2007 standard.
[0033] Table 1 , Example 1-4: 4-N, N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid containing carboxyl group is used as a hydrophilic chain extender. The obtained waterborne polyurethane has good dispersibility in water, the emulsion does not stratify, and has excellent storage stability. Copper ions and nanocellulose are added at the same time. The copper ions are respectively reacted with the pyridine-2-carboxylic acid ( ) forms a coordination effect with the hydroxyl group of nanocellulose, thereby playing the role of a cross-linking agent, ionically cross-linking the polyurethane and nanocellulose, improving the interfacial bonding properties of the polyurethane and nanocellulose, making the nanocellulose play a better reinforcement role, and the paint film has higher pencil hardness, impact resistance and mechanical properties. After ionic cross-linking, the polyurethane and nanocellulose form a tight molecular chain cross-linking network, which can inhibit water molecules and corrosive media such as acids, alkalis and salts from entering the interior of the polyurethane paint film, so that the paint film exhibits higher water resistance and salt spray resistance, and has better waterproof and anti-corrosion properties.
[0034] Compared with Example 1, Comparative Example 1 does not add copper ions, and the water-based polyurethane and nanocellulose cannot be ionically cross-linked, resulting in low interfacial bonding performance between polyurethane and nanocellulose, low pencil hardness, impact resistance and mechanical properties of the paint film, and poor water resistance and salt spray resistance.
[0035] Comparative Example 2 uses 4-N, N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid methyl ester as a chain extender, which does not contain a carboxyl group and cannot obtain a waterborne polyurethane, resulting in poor dispersibility in water, easy stratification of the coating, and poor storage stability. In addition, it does not contain a pyridine-2-carboxylic acid structure, which makes it difficult to coordinate and crosslink with the hydroxyl group of nanocellulose and copper ions, resulting in poor pencil hardness, impact resistance, water resistance, and salt spray resistance of the paint film.
[0036] In Comparative Example 3, conventional 2,2-dimethylolpropionic acid is used as a chain extender. The obtained water-based polyurethane does not contain a pyridine-2-carboxylic acid structure, has a low coordination effect with the hydroxyl group and copper ions of nanocellulose, and has weak ionic crosslinking performance, resulting in poor pencil hardness, impact resistance, water resistance and salt spray resistance of the paint film.
Claims
1. A preparation process of a waterproof coating for roads and bridges, characterized in that: The preparation process comprises the following steps: adding polyester polyol into a reaction container, adding isocyanate monomer and dibutyltin dilaurate after drying and dehydration, introducing nitrogen, heating to 70-80° C., reacting for 2-2.5 h, lowering the temperature to 40-45° C., adding acetone and 4-N,N-di(2-hydroxyethyl)aminopyridine-2-carboxylic acid, reacting for 40-60 min, adding water, nanocellulose and copper salt, stirring for 6-10 h, and finally adding a neutralizer, a pigment, a dispersant and a defoamer, shearing and dispersing, and obtaining a waterproof coating for roads and bridges.
2. The preparation process of the waterproof coating for roads and bridges according to claim 1, characterized in that: The molar ratio of the polyester polyol and the isocyanate monomer n(-OH):n(-NCO) is 1:(2.6-2.8).
3. The preparation process of the waterproof coating for roads and bridges according to claim 1, characterized in that: The molar ratio of the isocyanate monomer to 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid is 1:(1-1.1).
4. The preparation process of the waterproof coating for roads and bridges according to claim 2 or 3, characterized in that: The isocyanate monomer is any one of toluene-2,4-diisocyanate, isophorone diisocyanate, and 4,4'-diphenylmethane diisocyanate.
5. The preparation process of the waterproof coating for roads and bridges according to claim 1, characterized in that: The mass of the nanocellulose is 10-25% of the total mass of the polyester polyol, the isocyanate monomer and the 4-N,N-di(2-hydroxyethyl)aminopyridine-2-carboxylic acid.
6. The preparation process of the waterproof coating for roads and bridges according to claim 1, characterized in that: The mass of the copper salt is 0.5-1.4% of the total mass of the polyester polyol, the isocyanate monomer and the 4-N,N-di(2-hydroxyethyl)aminopyridine-2-carboxylic acid.
7. The preparation process of the waterproof coating for roads and bridges according to claim 1, characterized in that: The copper salt is cuprous chloride or copper nitrate.
8. The preparation process of the waterproof coating for roads and bridges according to claim 5 or 6, characterized in that: The preparation process of the 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid is as follows: (1) Add water, propionic acid and methyl 4-aminopyridine-2-carboxylate to a reaction vessel, add a tetrahydrofuran solution of ethylene oxide at 0-5°C, then react at 10-15°C for 18-30h, distill under reduced pressure, extract, and dry to obtain methyl 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylate; (2) Add 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid methyl ester and aqueous sodium hydroxide solution to methanol, heat to 85-90°C, condense and reflux for 5-8 hours, distill under reduced pressure, add hydrochloric acid dropwise to the aqueous phase to precipitate, filter, and dry to obtain 4-N,N-bis(2-hydroxyethyl)aminopyridine-2-carboxylic acid.
9. The preparation process of the waterproof coating for roads and bridges according to claim 8, characterized in that: The molar ratio of 4-aminopyridine-2-carboxylic acid methyl ester to ethylene oxide in (1) is 1:(2.4-3).
10. The preparation process of the waterproof coating for roads and bridges according to claim 8, characterized in that: The concentration of the sodium hydroxide aqueous solution in (2) is 2.8-4 mol / L.
Citation Information
Patent Citations
Flame-retardant modified polyurethane curing agent and its preparation method and two-component polyurethane coating
CN108610721B
Flame-retardant modified polyurethane curing agent as well as preparation method and two-component polyurethane coating
CN108610721A
Preparation method and application of cellulose nanocrystal modified waterborne polyurethane composite material
CN115894855A
Preparation method of modified waterborne polyurethane coating
CN118359988A
Antibacterial nano-cellulose-based waterborne polyurethane resin coating film and preparation method thereof
CN118725713A
Cited By
Degradable resin and preparation method thereof
CN120248277A